THE INFLUENCE OF FINANCIAL LITERACY AND FINANCIAL INCLUSION ON SMALL AND MEDIUM ENTREPRISES (SMEs) - Fauziah Buhari; Rismawati Rismawati; Imam Pribadi, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2024)
Small and medium-sized enterprises (SMEs) employ 97% of Indonesia's workers and account for more than 60% of the nation's GDP. The aim of this study is to examine the relationship among financial literacy, financial inclusion, and the performance of small and medium-sized businesses. Structured questionnaires were utilized to collect data from 380 SMEs utilizing a quantitative technique and a cross-sectional survey design. Financial inclusion and literacy were measured using five-point Likert scales. The statistical studies that were performed included descriptive analysis, reliability and validity tests, multiple regression, and Pearson correlation. The findings demonstrate that financial literacy and financial inclusion both positively impact SMEs' performance and complement one another. This study highlights the critical need for integrated policies and efforts that enhance financial literacy and inclusivity in order to promote the growth and sustainability of SMEs. It is distinctive in that it shows the beneficial relationship between these elements while promoting an all-encompassing approach to optimize the performance of SMEs in Indonesia.